Celebrating Adam Watkins' Third Birthday at Special Spot - Watkins, Howard::::::::: (1981)
Annie Tilley, Adam, Seth Tilley, Marshall Chambers, Clay ?, Devon Bleile-Kratzer; and co-teacher Sandy Jones seated at white children's table